2019
DOI: 10.3390/molecules24081549
|View full text |Cite
|
Sign up to set email alerts
|

Diamond Nanoparticles Downregulate Expression of CycD and CycE in Glioma Cells

Abstract: Our previous studies have shown that diamond nanoparticles (NDs) exhibited antiangiogenic and proapoptotic properties in vitro in glioblastoma multiforme (GBM) cells and in tumors in vivo. Moreover, NDs inhibited adhesion, leading to the suppression of migration and invasion of GBM. In the present study, we hypothesized that the NDs might also inhibit proliferation and cell cycle in glioma cells. Experiments were performed in vitro with the U87 and U118 lines of GBM cells, and for comparison, the Hs5 line of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…As shown in Figure 1 A, U87 cells grown in standard serum conditions (10% FBS) presented a doubling time of ca. 33 h, in agreement with previous reports [ 14 , 15 ], but the reduction of the serum concentration to 2% increased the cell-doubling time by 6 h. Under these rate-limiting conditions, the expression of SCD1 protein in U87 cells increased significantly ( Figure 1 B), as compared to that in cells grown in 10% FBS and in normal human astrocytes (NHAs). It should be noted that NHAs are commonly cultured under low serum [ 16 ], conditions that were also employed herein, by supplementing the culture medium with 2% FBS [ 17 , 18 ].…”
Section: Resultssupporting
confidence: 91%
“…As shown in Figure 1 A, U87 cells grown in standard serum conditions (10% FBS) presented a doubling time of ca. 33 h, in agreement with previous reports [ 14 , 15 ], but the reduction of the serum concentration to 2% increased the cell-doubling time by 6 h. Under these rate-limiting conditions, the expression of SCD1 protein in U87 cells increased significantly ( Figure 1 B), as compared to that in cells grown in 10% FBS and in normal human astrocytes (NHAs). It should be noted that NHAs are commonly cultured under low serum [ 16 ], conditions that were also employed herein, by supplementing the culture medium with 2% FBS [ 17 , 18 ].…”
Section: Resultssupporting
confidence: 91%
“…Proliferative ability of cells was also reduced (i.e., prolongation of doubling time) by nanodiamonds, shown for U87 and U118 glioblastoma cells via cell cycle arrest (Grodzik et al, 2019). Nanodiamonds arrested cells in the G 0 /G 1 phase after 72 hr incubation.…”
Section: Biological Mechanismsmentioning
confidence: 94%
“…Detonation-produced diamond nanoparticles, purchased from SkySpring Nanomaterials, have found extensive applications in various fields. One potential application of these compounds lies in their use to investigate undesirable cytotoxicity in normal cells and assess their ability to induce expected cytotoxic effects while also modulating the expression of factors that improve invasiveness in diverse cancer cell lines [ 38 , 39 , 40 , 41 ]. Furthermore, safety studies conducted on rats demonstrated that the intraperitoneal administration of 500 μg/mL of these diamond nanoparticles did not have any toxic effects on blood parameters or rat growth, suggesting their potential use as remedies or in drug delivery systems [ 42 ].…”
Section: Discussionmentioning
confidence: 99%